Pengaruh Pemanfaatan Teknologi Informasi dan Kompetensi Terhadap Efektivitas Audit Internal dengan Dukungan Manajemen Puncak sebagai Variabel Moderasi - Azizah, Idha; Farid, Nurul Fadhilah (Disclosure: Journal of Accounting and Finance, 2021)
The purpose of this research is to examine the factors that influence the Internal Audit Effectiveness conducted by staff or managers of internal auditors in Jakarta. The independent variabel of this research is Information Technology Usage, and Internal Auditor Competence, moderating variable of this research is Top Management Support. The method is using Moderated Regression Analysis (MRA). This research uses a questionaires distribute to 156 respondent using google form distributed to staff or managers of internal auditors in Jakarta.Â  The results of this research were as follows: Internal Auditor Competence and Top Management Supports are significantly positive effect with Internal Audit Effectiveness, Information Technology Usage has no effect with Internal Audit Effectiveness, Top Management Support does not moderate the relationship between Information Technology Usage and Internal Auditor Competence with Internal Audit Effectiveness.